Trade-Off Between Schooling and Labor for Children: Understanding the Determinative Factors Among Rural Households in Bangladesh - Islam, Rafiqul; Hoque, Md Mahmudul (Frontiers in Sociology, 2022)
This research is concerned with understanding the factors behind the trade-off between child labour and child schooling, given the well-documented links between the two. It examines parents’ behaviour in their decision-making on their children’s schooling or practicing child labour. Depending on qualitative research methods including 28 semi-structured interviews and two focus group discussions conducted in the rural areas of Bangladesh in 2020, this study reveals the following: subsistence needs compel households, particularly the ultra-poor and the female-headed, to trade off child labour with schooling; due to higher demand of labour, parents engage their children into work instead of schooling; parents of labour-intensive occupations tend to trade off child labour with schooling; sexual division of labour remains obvious; finally, credit constraints and cultural beliefs have negative impacts on parental decision-making on child schooling. Interventions aiming to reduce child labour and increase schooling in these rural areas must remain mindful of the socio-economic and cultural needs.